SAT0431 Inflammatory Ultrasound Features Show Strong and Independent Associations with Progression of Structural Damage after 2.5 Years of Follow-Up in Hand Osteoarthritis Patients. (10th June 2014) - Kortekaas, M.; Kwok, W.Y.; Reijnierse, M.; Kloppenburg, M.
Abstract : Background: Several cross sectional studies have shown that inflammatory ultrasound (US) features are frequently found in hand osteoarthritis (OA). Up till now, no follow up studies have been performed to study the natural evolution of inflammatory features and their association with structural damage. Objectives: To investigate the development of inflammatory US features and it's relation to structural damage over a 2.5 year period in 56 hand OA patients. Methods: Synovial thickening, effusion and power Doppler signal (PDS) in DIP, PIP, 1st CMC, MCP and 1st IP joints were assessed using ultrasonography (US) in 56 consecutive hand OA patients (mean age 61.2 years, 86% female) fulfilling ACR classification criteria, at baseline and follow-up. Progression of osteophytes and joint space narrowing (JSN) was scored using the OARSI atlas. With generalized estimated equations odds ratios (OR) with 95% confidence intervals (CI) were calculated for the associations between inflammatory US features and radiographic progression taking in account patient effect, age, gender, BMI, baseline osteophytes and JSN scores, and other inflammatory US features. Results: Of 1680 joints 8.4%, 8.7%, and 19.8% had synovial thickening, effusion or PDS at baseline, respectively, and 120 and 96 had progression of osteophytes and JSN, respectively. Independent associations were found between synovial thickening, effusion and PDS (grade 2-3 versus 0), and progression of osteophytes (OR (95%CI): 2.6 (1.02-6.5), 3.5 (1.7-7.4) and 5.7 (1.5-21.1)) and of JSN (OR (95%CI): 3.4 (1.3-8.4), 3.3 (1.5-7.6) and 3.1 (1.01-9.2)). Persistent inflammatory features at baseline and follow-up showed stronger associations with radiographic progression than fluctuating inflammatory features in comparison to no inflammatory features. Conclusions: Inflammatory US features, especially when persistently present, are independently associated with radiographic progression in hand OA after 2.5 years, indicating a role of inflammation in the aetiology of structural damage in hand OA. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2734